Implementation of Good Corporate Governance in Public Hospitals in Indonesia: Systematic Literature Review Approach - Dhiana Wijayanti; Christina Tri Setyorini (Poltanesa, 2023)
The purpose of this study was to conduct a thorough literature review to obtain a comprehensive understanding of the implementation and characteristics of good corporate governance in public hospitals. In February of 2022, a comprehensive evaluation of research findings published between 2018 and 2022 was conducted for this study. This study analyzed 51 documents after the screening procedure, of which 12 were relevant and 39 were irrelevant. The findings of this study indicated that the growth of hospital governance in Indonesia is primarily tied to patient satisfaction and hospital performance. In these studies, variables such as transparency accountability responsibility, independence, and impartiality are frequently mentioned, but organizational culture is also a crucial aspect of hospital governance. This study also identified the factors that facilitate or impede hospital governance implementation in Indonesia, particularly in public hospitals. Uncertainty in the regulations and laws regulating the implementation of public/government hospital governance is one of the contributing factors. Improving the implementation of hospital governance is crucial for improving the efficacy of Indonesian hospitals. By casting light on the key characteristics and challenges of hospital governance, the study provides valuable insights that can assist policymakers, healthcare administrators, and other stakeholders in enhancing corporate governance practices in public hospitals.